Effects of the lactation period, breed and feed on amino acids profile of mare’s milk - Fišera, Miroslav; Kráčmar, Stanislav; Šustová, Květoslava; Tvrzník, Pavel; Velichová, Helena; Fišerová, Lenka; Kubáň, Vlastimil (Potravinarstvo, 2020)
The effects of the lactation period, breed, and feed on amino acids profile of mare’s milk were investigated. The feed contained two major essential amino acids (EAAs) leucine (7.31 – 10.3 g.kg-1) and arginine (6.37 – 9.59 g.kg-1); it also included minor EAAs methionine (2.11 – 3.05 g.kg-1) and histidine (2.48 – 3.60 g.kg-1). Glu+Gln, Asp+Asn, and proline, major nonessential amino acids (NEAAs), constituted approximately 60% of total NEAAs (TNEAAs). The ratio of total EAAs to NEAAs ranged from 1:1.2 to 1:1.4. Amino acids (AA) content throughout all milk samples varied due to mare’s different conditions and lactation days. Except for the 1P milk sample, total AA content in the 2 – 8Ps specimens caused by differences in breed oscillated from the 2nd to 28th day of lactation within the following limits: 21.9 – 54.6 g.kg-1, 33.6 – 70.7 g.kg-1, 38.1 – 71.2 g.kg-1, 29.46 – 74.2 g.kg-1, 52.2 – 87.1 g.kg-1, 37.9 – 70.3 g.kg-1 and 26.4 – 64.5 g.kg-1, respectively. In relation to TEAAs in milk, the highest EAAs levels were reached in arginine, leucine and lysine ranging between 2.41 – 4.35 g.kg-1, 3.36 – 5.59 g.kg-1 and 2.72 – 4.80 g.kg-1, respectively, while the lowest AAs amounts were indicated in histidine and methionine, 0.91 – 1.58 g.kg-1 and 1.23 – 2.04 g.kg-1 respectively. Total NEAAs content was slightly higher than that of EAAs; the TNEAAs to TEAAs ratio was 1:0.9 proximately. Glu+Gln, Asp+Asn and proline were determined as major NEAAs of milk ranging between, 6.77 – 11.0 g.kg-1, 3.21 – 5.60 g.kg-1 and 1.25 – 2.18 g.kg-1, respectively; levels of NEAAs such as cysteine and glycine oscillated between 0.89 – 1.52 g.kg-1 and 0.64 – 1.15 g.kg-1, respectively. The average TAAs contents caused by breed differences were 62.8 g.kg-1, 42.8 g.kg-1, 44.7 g.kg-1 and 44.8 g.kg-1, respectively, on the 2nd, 5th, 10th, and 28th lactation days.